Dividend Payout Trends & Historical Analysis of Selected Cement Companies in India and Their Impact on Human Resource Development - Bai, R. Rethina; K. Hemalatha, K. Hemalatha (Journal of Neonatal Surgery, 2025)
The study will analyze changing trends of dividend payout and historical performance of these ten cement companies in India in the period 2015–16 to 2023–24, particularly how it impacts on human resource development. Dividend policy is a significant financial decision that affects the investor confidence, the corporate stability and the employee development. For any company, understanding the relationship between dividend strategies and human resource investments is key to continuous growth of the company. Earnings Per Share (EPS), Dividend Per Share (DPS) and Dividend Payout Ratio (DPR) will be considered in the study and will be used to assess the stability of financials and shareholder returns. The research looks at historical data to ascertain trends and corporate strategy in dividend distribution. The findings reveal UltraTech Cement as the top performer in the EPS with highest average EPS which signifies robust financial health and fairly balanced strategy towards earning and dividends. For example, HIL Cement has been able to maintain high and consistent dividend payout while Star Cement and Mangalam Cement have not maintained a constant dividend policy that might be a result of other financial management strategies used in each company. The impact of dividends policies on human resource development is indirect, and it is thus studied in this dissertation. Companies that affords stable and higher dividends will be more likely to invest in employee benefits, training program, performance incentives to improve workforce motivation and retention. Through this research, I offer a contribution to existing literature by linking financial performance to employee developing and highlighting how dividend policies play a role in both, creating shareholder value as well as organizational growth